2017
DOI: 10.11606/s1518-8787.2017051000069
|View full text |Cite
|
Sign up to set email alerts
|

The Geographic Information System applied to study schistosomiasis in Pernambuco

Abstract: OBJECTIVE Diagnose risk environments for schistosomiasis in coastal localities of Pernambuco using geoprocessing techniques.METHODS A coproscopic and malacological survey were carried out in the Forte Orange and Serrambi areas. Environmental variables (temperature, salinity, pH, total dissolved solids and water fecal coliform dosage) were collected from Biomphalaria breeding sites or foci. The spatial analysis was performed using ArcGis 10.1 software, applying the kernel estimator, elevation map, and distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
7
0
3
Order By: Relevance
“…The analysis of spatial distribution patterns indicated a higher concentration of cases and hospital admissions for schistosomiasis in areas along the coast of the states of Pernambuco, Alagoas, and Sergipe, corroborating other studies that revealed high morbidity and mortality rates due to the disease and the formation of clusters in these areas [30,[45][46][47][48]. Hospital admissions due to schistosomiasis result from the evolution of the disease, when there were failures in the identification of cases, timely treatment, and healthcare of the affected person [8].…”
Section: Discussionsupporting
confidence: 87%
“…The analysis of spatial distribution patterns indicated a higher concentration of cases and hospital admissions for schistosomiasis in areas along the coast of the states of Pernambuco, Alagoas, and Sergipe, corroborating other studies that revealed high morbidity and mortality rates due to the disease and the formation of clusters in these areas [30,[45][46][47][48]. Hospital admissions due to schistosomiasis result from the evolution of the disease, when there were failures in the identification of cases, timely treatment, and healthcare of the affected person [8].…”
Section: Discussionsupporting
confidence: 87%
“…Despite all the measures implemented by the PCE, as diagnosis and mass treatment of populations in endemic areas, schistosomiasis still has a high number of cases and deaths, and remains a serious public health concern in Brazil [ 6 , 11 , 20 ] . Herein, we conducted a pioneer, and population-based study, to assess the epidemiological profile and spatial and temporal patterns of deaths from schistosomiasis in Brazil, as basic and associated cause, in a period of 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this, assessing the basic and associated causes of death can improve to health systems, especially in mortality risk analysis. In that regard, temporal and spatial analysis techniques are one of the most efficient methods, since they allow to monitor the impacts of the disease over time and in space [ 9 , 11 ]. Several studies have used spatial and spatiotemporal analysis tools to comprehend the dynamics of schistosomiasis in Brazil [ 4 , 6 , 12 ].…”
mentioning
confidence: 99%
“…Uma alternativa para endossar estes achados laboratoriais é a investigação de indicadores externos que interfiram no processo saúde-doença com emprego de ferramentas de geoprocessamento, que enriquece o estudo (BARBOSA et al, 2017a), pois possibilita o cruzamento de informações biológicas e ambientais a variáveis sociopolíticas importadas de bancos de dados governamentais (DUTRA, 2011). Sendo assim, este estudo teve como objetivo principal analisar os fatores condicionantes envolvidos nos casos identificados na área de estudo e na transmissão da esquistossomíase no município de Ilhéus e projetar seus cenários por meio da análise espacial.…”
Section: Introductionunclassified